2014
DOI: 10.1371/journal.ppat.1004038
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Proteomics Reveals Elevated Muscle Proteins in Plasma of Children with Cerebral Malaria

Abstract: Systemic inflammation and sequestration of parasitized erythrocytes are central processes in the pathophysiology of severe Plasmodium falciparum childhood malaria. However, it is still not understood why some children are more at risks to develop malaria complications than others. To identify human proteins in plasma related to childhood malaria syndromes, multiplex antibody suspension bead arrays were employed. Out of the 1,015 proteins analyzed in plasma from more than 700 children, 41 differed between malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 52 publications
1
53
0
Order By: Relevance
“…All participating children from Ibadan were recruited under the direction of the Childhood Malaria Research Group (CMRG) at the Department of Pediatrics of the University College Hospital (UCH), Ibadan, Nigeria, as previously described (8)(9)(10)(11). Briefly, children were 6 months to 13 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…All participating children from Ibadan were recruited under the direction of the Childhood Malaria Research Group (CMRG) at the Department of Pediatrics of the University College Hospital (UCH), Ibadan, Nigeria, as previously described (8)(9)(10)(11). Briefly, children were 6 months to 13 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the intent of this study was to identify potential predictive and disease monitoring markers for severity in falciparum malaria. Comparative proteomic profiling of serum from healthy community controls and non-severe and severe falciparum malaria patients from different malaria endemic regions from India provided a plethora of information to complement the earlier similar proteomics studies reported on the African populations [10][11][12]20], and provided some novel mechanistic insights into the pathogenic mechanism for disease severity in P. falciparum infection (Fig. 3).…”
Section: Discussionmentioning
confidence: 69%
“…A series of studies over the past decade has provided valuable information regarding the proteomic alterations in human host in falciparum and vivax malaria [10][11][12]20,21]. In previously reported studies, differential abundance of multiple serum proteins including haptoglobin, serum amyloid A, serum albumin, apolipoprotein A-1, apolipoprotein E, alpha-2-macroglobulin, and vitronectin has been described in adults suffering from non-severe falciparum malaria [13,20] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased levels of AMFR found in plasma from osteoporosis patients may reflect a lower level of physical activity in osteoporotic patients, when considering that transcripts were abundant in skeletal muscle and mirroring a reduced turnaround in muscle proteins. In other recent studies on neuromuscular dystrophy 31 and childhood malaria 32, other muscle proteins have been detected in plasma as indicators of disease.…”
Section: Discussionmentioning
confidence: 99%